The Development Model Reducing Conflict with Multi-group Measurement for Policy from Enhancing Wellbeing of Personal in Multi-complex Organizations of Working Age - Parichat Yepitak ปาริชาติ เยพิทักษ์; Thirawat Chantuk ธีระวัฒน์ จันทึก; ศิริวงศ์ พิทักษ์ (Dusit Thani College Journal, 2018)
This research aims 1) to find variants of reducing conflicts measurements pluralism to enhance the well-being of the organization, a diverse range of working age, And 2) to study the development models for reducing conflict measurements pluralism to strengthen. A welfare organization with a diverse range of working age. The population of this research is the lecturer in Rajamangala university of technology. Using stratified random sampling. The sample of 1,380 people from the analysis of data by confirmatory factor analysis (CFA) data was collected from questionnaires that determine the validity (Construct Validity) variant of the six variables by means of confirmatory factor analysis. The first object to find that the six variables was transformational leaderships, Communication efficacy, organization Justice, team efficacy, reducing conflict and wellbeing. The second object to find that the development models for reducing conflict measurements pluralism to strengthen all variables consistent. This was consistent with empirical data. Harmonized index remained all variables. The observed that chi-square No statistically significant for all models. There were the comparative fit index (CFI) =.98, the relative fit index: RFI) =.98, the standard root mean square residual (SRMR) =.06, the root mean square error of approximation (RMSEA) = .06, the probability (p-Value) was lesser .01, the goodness of fit index (GFI) =.94, the adjust goodness of fit index (AGFI) = .93 and observed variables significant at all levels total .01